Single Mother Parenting Towards The Formation Of Early Childhood Independence - Rivo Panji Yudha; Marlina, Lina (Kirana Publisher (KNPub), 2025)
This research seeks to assess the impact of parenting styles employed by single mothers on the development of early childhood independence in the Kertasemaya District. An associative method with a quantitative approach is utilized for this study. The research will take place across various kindergartens situated in West Java Province. The population under consideration comprises all single mothers residing in Lemahayu Village, Kertasemaya District, Indramayu Regency, amounting to a total of 37 individuals, with total sampling being the chosen technique. Consequently, the sample encompasses all single mothers in Lemahayu Village, Kertasemaya District, Indramayu Regency, totaling 37 individuals. A questionnaire serves as the data collection instrument for this study. For data analysis, simple linear regression tests are conducted utilizing SPSS software. Findings indicate a significant effect of single mother parenting styles on early childhood independence in Kertasemaya District. The results from the simple regression test reveal a significance value of 0.049 (p<0.05), leading to the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (Ha). This signifies that the parenting styles of single mothers exert a substantial influence on the independence of children. In this study, the coefficient of determination (R²) reveals that the parenting styles of single mothers account for 78% of the variance in children's independence, with the remaining 22% attributed to other factors not explored in this research. These results suggest that the parenting style of single mothers plays a critically significant role in shaping children's independence.